Vocal cord palsy and getting to know it better - Gee Varghese, Irene; M. K., Goutham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Vocal cord palsy is a challenging entity encountered by otolaryngologists in clinical practice. It is a sign of an underlying pathology. Vocal cord palsy requires thorough examination and needs to be investigated. We conducted a study to identify the various etiology of vocal cord palsy and the various modalities of treatment. Methods: A prospective study was conducted to study the various etiologies and modalities of treatment of vocal cord palsy. A total of 55 patients with vocal cord palsy were included in our study based on the inclusion and exclusion criteria. Patients diagnosed with vocal cord paralysis were followed up and the various modalities of treatment were studied. Results: Males outnumbered females. Among patients of unilateral vocal cord paralysis left vocal cord was paralyzed in majority of the cases (30 patients). Vocal cord paralysis has a variable etiology. Neoplastic causes accounted for the largest number of patients followed by iatrogenic causes. The modality of treatment depends on the etiology. Patients with unilateral vocal cord palsy speech therapy were our modality of treatment. No surgical intervention was done for unilateral vocal cord palsy. Five patients with bilateral vocal cord palsy underwent Kashima’s operation. Conclusions: Vocal cord palsy is a symptom of an underlying disorder and not a disease. In our study malignancy is the commonest etiology for vocal cord palsy.